Explorations of antivalue in Francisco de Oliveira and David Harvey - Pereira, Paulo Cesar Xavier; Nakama, Vinicius; Gemal, Kamir Freire; Cunha, Tales Fontana Siqueira; Cevallos Serrano, Luis Andrés (Geografares, 2025)
This study examines the notion of antivalue in the works of Francisco de Oliveira and David Harvey, in dialogue with Marx, aiming to expand the theoretical understanding of the movements of value. The qualitative approach discusses and advances the conceptual elaboration of the authors, highlighting convergences and divergences in their conceptions. As a result, the triad of value, anti-value, and non-value is proposed as a contribution to the critical debate.
Keywords: triad; value; non-value